2011
DOI: 10.1590/s0037-86822011005000026
|View full text |Cite
|
Sign up to set email alerts
|

Contaminação do solo por ovos de geo-helmintos com potencial zoonótico na municipalidade de Fernandópolis, Estado de São Paulo, entre 2007 e 2008

Abstract: INTRODUÇÃO: A concentração de cães e gatos em áreas urbanas, associada a um número cada vez mais crescente da população errante desses animais, tem um papel epidemiológico importante na contaminação de solos de praças e parques públicos e na disseminação de infecções por variados gêneros de parasitas. O objetivo do presente estudo foi determinar a frequência de geo-helmintos com potencial zoonótico em solo de praças públicas e escolas municipais infantis da Cidade de Fernandópolis, Estado de São Paulo, Brasil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
2
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 10 publications
(8 reference statements)
1
21
2
22
Order By: Relevance
“…The numbers of eggs recovered ranged from 1 to 398 within the same sample. The contamination observed in this study was higher than what had previously been observed in other studies carried out in Brazil (SANTARÉM et al, 2010;CASSENOTE et al, 2011).…”
contrasting
confidence: 63%
See 1 more Smart Citation
“…The numbers of eggs recovered ranged from 1 to 398 within the same sample. The contamination observed in this study was higher than what had previously been observed in other studies carried out in Brazil (SANTARÉM et al, 2010;CASSENOTE et al, 2011).…”
contrasting
confidence: 63%
“…eggs (CAPUANO;ROCHA, 2005;SANTARÉM et al, 2010;CASSENOTE et al, 2011). Previous studies have considered that contact with soil is a risk factor for toxocariasis in humans.…”
mentioning
confidence: 99%
“…larvae. On the other hand, the degree of contamination by hookworm was higher than recovered in some cities, such as Fernandópolis, São Paulo (1.8%) 5 , Santos, São Paulo (15%) 35 , Duque de Caxias, Rio de Janeiro (33.5%) 42 and Araçatuba, São Paulo (37.5%) 28 . In contrast, contamination rates higher than our results were noted in Santa Maria (Rio Grande do Sul State) by CORRÊA & MOREIRA (1996) 8 , who found 93.3% of the public squares' land contaminated with eggs of Ancylostoma spp.…”
Section: Discussionmentioning
confidence: 76%
“…have been found in soil samples worldwide. They are present in public and private 13 , Kaduna, Nigeria (50.4%) 22 , Prague, Czech Republic (20.4%) 14 , Sapporo, Japan (7.47%) 25 and London, United Kingdom (6.3%) 15 as well as in different regions of Poland (2-37%) 26 and Spain (3.8-52%) 10 7 , Fernandópolis (20.89%) 5 , Ribeirão Preto (20.5%) 3 and Botucatu (17.5%) 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation